Idiopathic pupillary capture 7 years after extracapsular cataract extraction and intraocular lens implantation - Ramos, Juan; Jurado, Venancio (Digital Journal of Ophthalmology, 2011)
Pupillary capture is a pathology commonly associated with traumatic or inflammatory processes of the eye. We present a case of idiopathic pupillary capture, 7 years after extracapsular cataract extraction and intraocular lens implantation. This case highlights the need for ongoing patient surveillance, especially in elderly patients who are less able to detect subtle changes in their vision.